Impact of thermal sensation on exercise performance in the heat: a thermo tokyo sub-study - Kroesen, S. H.; de Korte, J. Q.; Hopman, M. T.; Bongers, C. C.; Eijsvogels, T. M. (European Journal of Applied Physiology, 2022)
Purpose Thermal perception, including thermal sensation (TS), influences exercise performance in the heat. TS is a widely used measure and we examined the impact of initial TS (iTS) on performance loss during exercise in simulated Tokyo environmental conditions among elite athletes.